Effects of dietary inclusion of alfalfa meal on productive performance, carcass and weight of digestive and lymphoid organs in organic type broiler chicken - Paredes A., Manuel (2020)
Two hundred and forty Hubbard female broilers were used from 35 to 84 days of age to study the effects of alfalfa meal (HA) on the productive performance, carcass characteristics, weight of digestive organs and weight of lymphoid organs. Chickens were bred in the Andean valley of Cajamarca, Peru, at 2750 meters above the sea level, fed diets containing three levels of HA as a partial replacement for corn, soybean meal and rice bran for 49 days. The birds were distributed in three treatments T0 (0% alfalfa meal), T1 (5% alfalfa meal) and T2 (10% alfalfa meal), each treatment with 4 repetitions of 20 birds each. The birds were slaughtered at 12 weeks of age. The body weight gain obtained was different (p<0.05) between treatments (77.4, 76.2 and 72.1 g/day for T0, T1 and T2, respectively). There were no differences between treatments in terms of consumption, feed conversion and carcass yield; however, differences were found (p<0.05) for relative weight of abdominal fat (T0: 2.30, T1: 2.60 and T2: 2.89%), relative weight of gizzard (T0: 1.00, T1: 1.03 and T2: 1.19%) and relative weight of intestines (T0: 2.26, T1: 2.38 and T2: 2.69%). No effect of HA on the weight of the lymphoid organs was found.